Chimera states in coupled Hindmarsh-Rose neurons with α-stable noise. (July 2021) - Wang, Zhanqing; Xu, Yong; Li, Yongge; Kapitaniak, Tomasz; Kurths, Jürgen
Highlights: α -stable noise is considered in Hindmarsh-Rose neuronal network, and chimera states can be observed. The strength of coherence is able to identify the occurrence of chimera states and the proportion of coherent neurons. The stability parameter and intensity of α -stable noise can suppress chimera states. Abstract: In this paper, we study α -stable noise-induced chimera states in a small-world Hindmarsh-Rose neuronal network. Chimera states are the coexistence of coherence and incoherence. The α -stable noise is a general non-Gaussian noise, and can be used to describe more complex and changeable noisy environments. We focus on the effect of the parameters of the small-world network (the rewiring probability) and α -stable noise (the stability parameter and noise intensity) on the chimera state. We find that the changes of the rewiring probability, the stability parameter and noise intensity can make the location and range of the incoherence domain for the chimera state shift and change, and changes of the stability parameter and noise intensity even make chimera state disappear. Moreover, we propose the strength of coherence based on the local order parameter, and it can be used to identify not only the occurrence of chimera states but also the proportion of coherent neurons in the entire network.